2022
DOI: 10.1007/s10730-022-09488-6
|View full text |Cite
|
Sign up to set email alerts
|

From Prohibition to Permission: The Winding Road of Medical Assistance in Dying in Canada

Abstract: In this paper, I offer a personal and professional narrative of how Canada went from prohibition to permission for medical assistance in dying (MAiD). I describe the legal developments to date and flag what might be coming in the near future. I also offer some personal observations and reflections on the role and impact of bioethics and bioethicists, on what it was like to be a participant in Canada's law reform process, and on lessons that readers in other jurisdictions might take from Canada's experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…As noted in the Method section, Canada’s MAiD law is set at the highest level through the Criminal Code , which is under the jurisdiction of the federal Parliament. 9 Implementation is then regulated through court cases and is regulated and systematized at the provincial/territorial, regional and local levels through provincial/territorial governments, regulatory bodies, MAiD programs, healthcare institutions and communities of practice. This theme reflects participants’ integration of Bill C-7 into practice, as well as consequential alterations to other regulations and system guidance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted in the Method section, Canada’s MAiD law is set at the highest level through the Criminal Code , which is under the jurisdiction of the federal Parliament. 9 Implementation is then regulated through court cases and is regulated and systematized at the provincial/territorial, regional and local levels through provincial/territorial governments, regulatory bodies, MAiD programs, healthcare institutions and communities of practice. This theme reflects participants’ integration of Bill C-7 into practice, as well as consequential alterations to other regulations and system guidance.…”
Section: Resultsmentioning
confidence: 99%
“…Bill C-7 also introduced amendments prompted by advocacy efforts and evidence about barriers in practice under Bill C-14. 9 These changes included removing the 10-day waiting period for Track 1 patients, streamlining witnessing requirements for the written request and permitting two types of advance requests for MAiD in limited circumstances (a ‘final consent waiver’ and ‘advance consent for failed self-administration’). Finally, Bill C-7 temporarily excluded access to MAiD for persons with mental disorder as their sole underlying medical condition (MAiD MD-SUMC).…”
Section: Introductionmentioning
confidence: 99%
“…This recognized that the removal of death must be in the foreseeable future, as well as narrowing eligibility so that the person must suffer from a serious and incurable illness, disease, or disability. Canadians reported that they felt the process and criteria seemed relatively easy and uncontroversial (Downie, 2022). Notably, the most controversial element of this bill was the black-and-white definition created for a grievous and irremediable medical condition.…”
Section: Implications For Health Social Work Professions and Familiesmentioning
confidence: 99%
“…Notably, the most controversial element of this bill was the black-and-white definition created for a grievous and irremediable medical condition. Due to these changes, some individuals are no longer eligible under new federal legislation, causing constitutional law scholars to testify before the House and Senate committees reviewing the bill (Downie, 2022).…”
Section: Implications For Health Social Work Professions and Familiesmentioning
confidence: 99%
“…• How have ethicists and ethics services participated in the introduction of MAiD in Canada over the first 6 years-both in the legal process that led to the current MAiD legislation (Downie 2022), and in addressing it as a novel organizational ethics challenge (Frolic & Miller, 2022;Bouthillier et al 2022)?…”
Section: Beyond the Norm(ative): Exploring The Practical Ethics Of Ma...mentioning
confidence: 99%